Neuromuscular Parameters Predict the Performance in an Incremental Cycling Test - García-García, Oscar; Cuba-Dorado, Alba; Fernández-Redondo, Diego; López-Chicharro, José (International Journal of Sports Medicine, 2018)
The aim was to determine the predictive capacity of neuromuscular parameters on physiological predictors of performance related to pedaling power. The sample comprised fifty elite cyclists. On the same day, they were given a neuromuscular evaluation with tensiomyography (TMG) and then performed an effort test on a cycle ergometer until exhaustion. The TMG recorded the maximum radial muscle belly displacement, contraction time, delay time, derivative normalized response speed, and lateral symmetry. Peak power output (Wpeak·kg−1), effort time, maximum lactate concentration, power in the first lactate threshold, and power in the second lactate threshold were recorded in the effort test. Linear regression analysis was used to determine the explanatory capacity of neuromuscular parameters on potential cycling performance indicators. A higher Wpeak·kg−1 during a maximal incremental test on the cycle ergometer can be predicted moderately (R2=0.683; R2a=0.615; R=0.826; Std. Error=0.26017; p<0.001) by a longer rectus femoris contraction time and a greater radial muscle belly displacement of the vastus lateralis and vastus medialis as well as a slower normalized response speed of the biceps femoris. In conclusion, neuromuscular parameters can partially explain performance in a specific cycling test until exhaustion.
Keywords: contractile properties; cycling performance; elite cyclist; fitness; peak power output; tensiomyography